2000
DOI: 10.1002/(sici)1522-726x(200003)49:3<253::aid-ccd5>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Response of the radial artery to three vasodilatory agents

Abstract: We examined the response of the radial artery to vasoactive agents (isosorbide dinitrate, ISDN, 1 mg, 3 mg, and 5 mg; verapamil, 1 mg, 3 mg, and 5 mg; and lidocaine, 10 mg, 30 mg, and 50 mg) in 100 consecutive patients admitted for elective coronary angiography. The drug solutions were directly injected into the radial artery from the puncture site. As a result, 5 mg of ISDN increased the diameter of the radial artery by 31% and 28.8% at the proximal and distal sites, respectively. Similarly, 5 mg of verapamil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
2

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 8 publications
1
16
0
2
Order By: Relevance
“…[17][18][19] Dentre outros fatores de prevenção, a utilização de várias drogas com efeito vasodilatador tem se mostrado eficaz em vários estudos 7,8,[20][21][22] , além da utilização de introdutores hidrofílicos, que promovem menor reação inflamatória tecidual local por menor trauma mecânico à parede arterial. Em estudo randomizado recente, Rathore et al 14 avaliaram 790 pacientes submetidos a intervenção coronária percutânea que utilizaram introdutores hidrofílicos e não-hidrofílicos e encontraram diminuição de cerca de 50% da incidên-cia de espasmo com a utilização dos introdutores recobertos.…”
Section: Discussionunclassified
“…[17][18][19] Dentre outros fatores de prevenção, a utilização de várias drogas com efeito vasodilatador tem se mostrado eficaz em vários estudos 7,8,[20][21][22] , além da utilização de introdutores hidrofílicos, que promovem menor reação inflamatória tecidual local por menor trauma mecânico à parede arterial. Em estudo randomizado recente, Rathore et al 14 avaliaram 790 pacientes submetidos a intervenção coronária percutânea que utilizaram introdutores hidrofílicos e não-hidrofílicos e encontraram diminuição de cerca de 50% da incidên-cia de espasmo com a utilização dos introdutores recobertos.…”
Section: Discussionunclassified
“…Abe et al found that ISDN was most potent vasodilator compared to verapamil, lignocaine and placebo [12]. While this study examined multiple doses, it was underpowered across each group.…”
Section: Other Outcomesmentioning
confidence: 95%
“…There are several studies that are significantly underpowered. There were as low as 30 patients in one study [15] and has low as 10 patients in each arm in another study [12]. Furthermore, many of the included studies were not fully published and were only available in abstract form.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…Isosorbide dinitrate is more effective than verapamil and lidocaine for radial artery dilatation. 19,20) Severe radial vasospasms occurred in 50% of patients and more frequently involved patients with a small radial artery diameter. We encountered one case with radial artery narrowing during the chronic phase.…”
Section: Vol 45mentioning
confidence: 99%